El cultivo de arroz y el desarrollo del turismo comunitario en el distrito Guadalupe, provincia Pacasmayo, región La Libertad - Guayán Castillo, María Lucía (2022)
This thesis entitled The cultivation of rice and the development of community tourism_x000D_ in the district of Guadalupe, Pacasmayo province, La Libertad region; with the variables_x000D_ contrasted in the field referring to the social, cultural and economic conditions. The_x000D_ social condition is evidenced in the existence of community organizations originated_x000D_ due to the transcendence of this crop, such as the Association of Irrigation Farmers with_x000D_ Intermittent Droughts (AARSI) and other cultural groups such as Muchik and Arte_x000D_ Pueblo. The cultural condition is sustained by its historical significance and the cultural_x000D_ practices originating from the cultivation process. The economic condition as part of_x000D_ local development is based on improving the quality of life, since rice cultivation is the_x000D_ main source of income for local producers, being a product with a high market share at_x000D_ the national level. This research was carried out to determine the conditions that rice_x000D_ cultivation presents for the development of community tourism in the reality of study._x000D_ For the fulfillment of the objectives, the ethnographic, analytical-synthetic and_x000D_ inductive-deductive methods were applied, applied for the analysis of the elements on_x000D_ the traditional cultivation of rice for their linkage and integral analysis. As for the_x000D_ applied techniques, it is the interview to collect information from the farmers about the_x000D_ rice cultivation process, as well as the representatives of the Muchick and Arte Pueblo_x000D_ cultural associations.